2004
DOI: 10.1128/mcb.24.12.5223-5234.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein 1 Induces Synthesis of Hypoxia-Inducible Factor 1α

Abstract: . Moreover, LMP1 induces HIF-1 DNA binding activity and upregulates HRE and VEGF promoter transcriptional activity. Finally, LMP1 increases the appearance of VEGF protein in extracellular fluids; induction of VEGF is suppressed by PD98059 or catalase. These results suggest that LMP1 increases HIF-1 activity through induction of HIF-1␣ protein expression, which is controlled by p42/p44 MAPK activity and H 2 O 2 . The ability of EBV, and specifically its major oncoprotein, LMP1, to induce HIF-1␣ along with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
214
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(233 citation statements)
references
References 63 publications
12
214
1
4
Order By: Relevance
“…In addition, COX-2 demonstrates a positive regulatory role in lymphangiogenesis [39] . Interestingly, all these factors are induced by the EBV-associated oncoprotein, LMP1, in NPC [8,29,30] . Thus, we expected that LMP1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, COX-2 demonstrates a positive regulatory role in lymphangiogenesis [39] . Interestingly, all these factors are induced by the EBV-associated oncoprotein, LMP1, in NPC [8,29,30] . Thus, we expected that LMP1…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed a significant relationship between angiogenesis and advancement of nodal status in NPC tissues [6,7] . Furthermore, we reported that latent membrane protein 1 (LMP1), an EBV-associated oncoprotein, induces angiogenic factors including vascular endothelial growth factor (VEGF)-A, interleukin (IL)-8, and fibroblast growth factor (FGF)-2 [6][7][8] . Thus, LMP1 plays a central role in angiogenesis, which results in progression of lymph node metastasis in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…A relation between LMP1 expression and increased HIF-1a expression was found by Wakisaka et al [14] in both lymphoblastoid and epithelial cell lines. Subsequently Kondo et al [15] showed the mechanism by which LMP1 functions-it stabilizes SIAH1, an E3 ubiquitin ligase, which in turn ubiquitinates and destabilizes prolyl hydroxylase proteins (PHD1 and PHD3) that, under normoxic conditions, are responsible for hydroxylation and subsequent degradation of HIF-1a.…”
Section: Introductionmentioning
confidence: 57%
“…Prior studies showed that LMP1 transfection of lymphoblastoid and carcinoma cell lines induced HIF-1a in vitro [14,15]. If the same pathway were active in vivo, it might compel clinical trials of newly available antiangiogenic agents to thwart the effects of LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…The herpesvirus Epstein Barr virus (EBV) is linked to development of nasopharyngeal carcinoma in specific populations. The major oncoprotein of EBV, latent membrane protein 1 (LMP1), increases HIF-1α levels and stimulates VEGF expression in nasopharyngeal epithelial cells through a mechanism dependant both upon H 2 O 2 production and p42/ p44 MAPK activity [43]. Recent co-immunoprecipation studies indicate EBV LMP1 enhances the stability of Siah1 E3 ubiquitin ligase, inducing proteasomal degradation of PHD-1 and PHD-3 that normally tag HIF-1α for degradation.…”
Section: Hif-1α Dynamics In Viral Infectionmentioning
confidence: 99%